Atherosclerotic patients with diabetes mellitus may break through the threshold of healthy TMAO levels formed by long-term statins therapy. Issue 2 (February 2023) - Liang, Hao; Yu, Anqi; Wang, Zheng; Zhang, Na; Wang, Qingsong; Gao, Haichao; Gao, Junhui; Wang, Xinjun; Wang, Hong
Abstract: Background: Cardiovascular disease (CVD) is the leading course of disease-related death in both developed and developing countries. Atherosclerosis is main pathology of CVD, and its severity is thought to be related to trimethylamine N-oxide (TMAO) level in plasma. Therefore, it is necessary to deeply understand the synergistic patterns between TMAO and other contribution variables to atherosclerosis, allowing for effective and timely monitoring or intervention. Methods: A total of 359 participants were recruited in our study, including 190 atherosclerosis patients, 82 MI or stroke patients, 68 non-atherosclerosis controls and 19 healthy controls. Information on their risk associated with atherosclerosis and plasma TMAO concentration were collected. LASSO regression, multivariate analysis and univariate analysis were then performed to confirm the correlation between TMAO level and risk factors of atherosclerosis. Results: Compared to patients and non-atherosclerosis controls, healthy participants had a normal BMI range (lower than 24), lower triglyceride concentration, and healthy lifestyle habits (no smoking and low salt diet). However, under backgrounds of statins treatment and balanced dietary preferences, TMAO levels were not significantly different among patients, non-atherosclerosis controls and healthy controls. Using LASSO regression model, four indicators was identified to have contribution to TMAO levels, including diabetes, atherosclerosis, low-density lipoprotein and total cholesterol. Subsequent univariate analysis further confirmed that the presence or absence of diabetes had a decisive effect on patients' plasma TMAO levels, even though they had been taking statin lipid-lowering drugs for a long time. Conclusion: Diabetics have abnormally high plasma TMAO levels even under continuous statins treatment, which may contribute to the development and progression of atherosclerosis. Therefore, it is necessary to focus on monitoring TMAO levels in diabetic patients to reduce adverse cardiovascular events in diabetic patients.